Integrative Transcriptomics and Metabolomics Analysis of Body Color Formation in the Leopard Coral Grouper (Plectropomus leopardus) - Zhu, Xiaowen; Hao, Ruijuan; Tian, Changxu; Zhang, Junpeng; Zhu, Chunhua; Li, Guangli (Frontiers in Marine Science, 2021)
Body color is an important economic and ecological trait in aquatic animals, which influence their economic values and determine the animal ability to survive in the marine environment. Red-colored Plectropomus leopardus is in high demand owing to its bright color and potential value for artificial breeding. High-throughput transcriptome sequencing and liquid chromatography tandem-mass spectrometry (LC-MS/MS) approaches were used to identify transcript and metabolic differences between black-colored and red-colored P. leopardus. Compared with the black-colored group, 218 and 181 differentially expressed genes were up- and down- regulated, respectively, in the red-colored group. 425 and 56 significantly different metabolites were identified in LC-MS positive and LC-MS negative ion models, respectively, between two colored groups. Based on the integrative analysis, the red-colored group exhibited greater carotenoid uptake, transport, and accumulation activity potential than those in the black-colored group and may consume more arachidonic acid for body color formation. The black-colored group showed greater melanin synthesis activity compared with the red-colored group. These results substantially improve the understanding of molecular and metabolic mechanisms underlying body color formation in P. leopardus and the potential of body color for the environment adaptation.